KADAR SERUM GLUTAMATE PIRUVAT TRANSAMINASE PECANDU MINUMAN KERAS DI BANJAR AMBENGAN DESA SAYAN UBUD GIANYAR - nyoman mastra; I Gusti Ayu Tari Diva Pradnya Dewi; I Wayan Merta (Meditory : The Journal of Medical Laboratory, 2016)
Background Banjar Ambengan is one banjar contained in Sayan village, where people still have the habit of gathering accompanied by excessive alcohol consumption. Consumption of alcohol has a direct relationship with the death cases caused by liver sirosis. The liver mechanism disturbance leads to the case of swelling as the result of the rise of serum glutamate piruvat transminase (SPGT) enzyme. Objective This study is aimed at investigating the SPGT level of the serum of the alcoholic. The study uses the non-probability sampling technique called snowball sampling. The samples of this study are thirty alcoholic men aging upper eighteen. The respondents will be interviewed to get the deeper information. The research reveals that 6 respondents have high SPGT level (20%) and 24 of them have normal SPGT level (80%). Result of the examination serum SGPT levels alcoholics in the study ranged from 11 to 79.20 U / L. The measurement results SGPT levels are high on the research respondents based on the characteristics of age at most 33.3%, based on the frequency of consumption of at most 33.3%, based on the period of consumption at most 50%, based on the volume of consumption at most 66.7%, based on the type of liquor consumed at most 66.7%, and based on the type of work at most 50%. Conclusion Keywords: Liquor, Liver, Addict, SGPT Levels